Nitric oxide acts downstream of reactive oxygen species in phytomelatonin receptor 1 (PMTR1)-mediated stomatal closure in Arabidopsis - Wang Z.; Li L.; Khan D.; Chen Y.; Pu X.; Wang X.; Guan M.; Rengel Z.; Chen Q.
Reactive oxygen species (ROS) and nitric oxide (NO) are important signaling molecules regulating stomatal movements in plants. Melatonin (N-acetyl-5-methoxytryptamine) was found to induce stomatal closure via phytomelatonin receptor 1 (PMTR1)-mediated activation of ROS production. Here, we evaluated the interaction between ROS and NO in the melatonin-induced stomatal closure in Arabidopsis. The results showed that the exogenous melatonin-induced stomatal closure and NO production were abolished by carboxy-PTIO (cPTIO, a NO scavenger). Additionally, the mutant lines nitrate reductase 1 and 2 (nia1nia2) and NO-associated 1 (noa1) did not show melatonin-induced stomatal closure, indicating that the melatonin-mediated stomatal closure is dependent on NO. The application of H2O2 induced the NO production and stomatal closure in the presence or absence of melatonin. However, the melatonin-induced NO production was impaired in the rhohC and rbohD/F (NADPH oxidase respiratory burst oxidase homologs) mutant plants. Furthermore, the ROS levels in nia1nia2 and noa1 did not differ significantly from the wild type plants, indicating that NO is a downstream component in the melatonin-induced ROS production. Exogenous melatonin did not induce NO and ROS production in the guard cells of pmtr1 mutant lines, suggesting NO occurs downstream of ROS in the PMTR1-mediated stomatal closure in Arabidopsis. Taken together, the results presented here suggest that melatonin-induced stomatal closure via PMTR1-mediated signaling in the regulation of ROS and NO production in Arabidopsis. © 2023 Elsevier GmbH
Keywords: ARABIDOPSIS THALIANA; MELATONIN; NITRIC OXIDE; PMTR1; ROS; STOMATAL CLOSURE